2017
DOI: 10.1590/s0100-736x2017001000006
|View full text |Cite
|
Sign up to set email alerts
|

Situação epidemiológica da anemia infecciosa equina em equídeos de tração do Distrito Federal

Abstract: RESUMO.-A anemia infecciosa equina (AIE) é uma doença causada por um lentivirus que possui distribuição mundial. Essa enfermidade é um entrave ao desenvolvimento da equinocultura no Brasil devido à obrigatoriedade de eutanásia dos animais positivos. Este trabalho teve como objetivo estimar a prevalência de AIE em equídeos de tração no Distrito Federal, assim como identificar fatores de risco associados à doença. Foram sorteados aleatoriamente 350 proprietários (Unidades Primárias de Amostragem-UPA) e foram amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
5
1
3
Order By: Relevance
“…The most significant association between the mules observed in this study was probably due to the habitat related to the concentration of insect vectors, the significant presence of asymptomatic animals, non-compliance with legislation by breeders, and how the animals are used. This fact is consistent with the prevalence observed in Distrito Federal (MORAES et al, 2017), where there was a superiority in seroreactivity mules (11.11%) compared with horses (1.46%).…”
Section: Discussionsupporting
confidence: 90%
“…The most significant association between the mules observed in this study was probably due to the habitat related to the concentration of insect vectors, the significant presence of asymptomatic animals, non-compliance with legislation by breeders, and how the animals are used. This fact is consistent with the prevalence observed in Distrito Federal (MORAES et al, 2017), where there was a superiority in seroreactivity mules (11.11%) compared with horses (1.46%).…”
Section: Discussionsupporting
confidence: 90%
“…However, MORAES et al (2017) conducted a study on working Equidae in the Federal District and found a prevalence of 1.81%. Although, the prevalence in the present study was 6 times higher than that observed by MORAES et al (2017), we emphasized that the animals seized in this study were not seized as roaming animals. Nevertheless, they were in a similar situation as those in the present study; that is, they were traversing the streets and without constant screenings despite having owners, approximately 80% of whom declared having knowledge of EIA.…”
Section: Some Regions Have Low Levels Of Infection Such Ascontrasting
confidence: 81%
“…As medidas de controle e erradicação consistem no sacrifício dos animais positivos e controle do foco. É uma zoonose acidental de caráter ocupacional, rara e fatal (ALIBASOGLU et al, 1986;ITO et al, 2008;DIEHL, 2013;MORAES, 2011).…”
Section: Resultsunclassified